Nutrition management and early rehabilitation in ICU pregnant with hyperemesis gravidarum complicated by central pontine myelinolysis: A case report - Antonella Cotoia; Giuseppe Ferrara; Michela Rauseo; Michela Brattoli; Lea Pia Cantatore; Stefania Da Lima; Marcello Chinni; Chiara Ciritella; Lucia Mirabella; Gilda Cinnella (Clinical Nutrition Open Science, 2024)
Summary: Our case report aims to highlight the multidisciplinary approach adopted for the avoidance of ICU-acquired weakness and the assessment of nutritional therapy in 16 weeks young pregnant with diagnosis of hyperemesis gravidarum complicated with central pontine myelinolysis, after the development of acute respiratory failure due to pneumonia.Thiamine and electrolytes were properly supplemented to minimize the high risk of developing refeeding syndrome. Due to severe nausea and vomiting, antiemetic therapy was started and a parenteral route was chosen during the first two days of non-invasive ventilation. On day three, the patient was intubated and mechanically ventilated due to severe respiratory failure, semi-elemental formula was started by enteral route while parenteral nutrition was supplemented and early rehabilitation was started. Antiemetic therapy was continued until day 28th when the pregnant woman was shifted to oral nutrition only. On day 87th the postpartum mother was transferred to the rehabilitation center for an intensive rehabilitative program based on the motor recovery of lower limb and swallowing recovery.